Pizza in his pocket - Abdul jawwad ,Rahman (Good word kidz, 2003)
"Pizza in His Pocket" is a children's book written by Zain Bhikha. It uses fun rhymes and colorful illustrations to teach kids about the importance of sharing, gratitude, and helping those in need. The story follows a boy who loves to eat all kinds of food, especially pizza, but soon learns a valuable lesson about excess and the joy of giving to others$1 (Bespecially to those who don$1 (Bt have enough. It's a lighthearted yet meaningful story with an Islamic moral message about generosity and caring for the poor.s